Decay rates of two tracer gases compared to DNA-tagged liquid aerosol tracer particles: Impact of varying dilution rate and filtration. (15th March 2022) - Arvelo, Ilan; Pagone, Frank; Persky, Jacob; Carpio, Carlos E.; Arnold, Phil; Clements, Nicholas
Abstract: Current gas-and aerosol-based tracers do not adequately simulate the emission and transport of liquid aerosols containing a pathogen indoors. To evaluate a liquid aerosol tracer containing synthetic DNA, the tracer was emitted in a chamber to measure changes in decay rates as outdoor air dilution rate and filter rating varied. DNA tracer concentration decay rates were compared to decay rates of size distributions of liquid tracer aerosols and two tracer gases (CO2 and SF6 ) to characterize the evolution of the particle size distribution simulated by the aerosols containing DNA tracer compared to common air change rate measurements. The effect of dilution ventilation on tracer decay rates was assessed at four air change rates using HEPA-filtered outdoor air (0, 1.3, 2.5, and 4.2 ACH), and the simultaneous impact of filtration of recirculated air (0, 1.3, 2.5, and 4.2 ACH) was tested using MERV8 and MERV13 filters. DNA tracer concentrations decayed at a rate comparable to liquid aerosols of 5–25 μm in diameter. Filter type did not consistently impact the rate of coarse particle or DNA tracer removal, though differences were observed for fine aerosols. Results indicate DNA-tagged tracer aerosols can simulate liquid aerosol emission and transport in a room, and the effectiveness of aerosol control strategies can be evaluated by observing the decay rate of DNA tracer concentrations. Highlights: DNA-tagged tracer aerosols simulate liquid aerosol emission and transport indoors. DNA-tagged aerosol decay rates were compared to CO2 and SF6 decay rates. DNA tracer concentrations decayed at a similar rate as 5–25 μm aerosols. Ventilation effectively reduced DNA-tagged aerosols and tracer gas concentrations. Filter MERV-rating did not consistently impact liquid aerosol decay rates.